Eksplorasi Elemenintegrated Reporting Dalam Annual Reports Perusahaan Di Indonesia - Anis Chariri; Indira Januarti (Jurnal Akuntansi, 2017)
This study aims to identify the patterns and scope of integrated reportingand toexamine the effect of audit committee characteristics (expertise and meeting) onelementsof integrated reporting disclosed in the annual report of companies listed on the IndonesiaStock Exchanges (IDX). This study used 170 annual reports of companies listed on theIDX as research data (not all companies have the required data). Research data were thenanalyzed using STATA / MP14 Software. The findings showed that the IDX-listedcompanies have presented annual reports in accordance with the elements of integatedreporting although the scope of presentation was relatively low amounting of51% (33 of64 indicators). Furthermore, this study revealed that the audit committees’ expertise (inaccounting/ finance) and the frequency of audit committee meetings positively andsignificantly influenced the scope of the integrated reportingpresented in the annual reportof the companies.